Differenzialdiagnose der kindlichen Anämie - Kunz, Joachim; Kulozik, Andreas (Monatsschrift Kinderheilkunde, 2012)
The diagnosis of childhood anemia requires a blood cell count with regard to the age-related reference range. In addition to the medical history and physical examination, a complete blood count supplies information which allows a classification of the anemia and often a definitive diagnosis. Further targeted laboratory examinations beyond a mechanical blood cell count may be required in a second step.
Gesehen am 06.11.2018